The Effect of Social Media Usage on Visiting Intentions: The Moderating Role of Influencer Following Behavior Among Generation Z in Indonesia - Maulana Rachmandani, Ilyasa Irfan; Kusumah, Ahmad Hudaiby Galih; Sukriah, Erry (E-Journal of Tourism; Volume 12 Number 1 (March 2025)DO - 10.24922/eot.v12i1.125161, 2025)
Social media is one of the primary sources for Generation Z in seeking travel information and inspiration. This study aims to understand the relationship between social media usage goals and visit intentions, and to examine the moderating role of following social media influencers. The study used quantitative methods by distributing questionnaires to 212 respondents. Hypothesis testing was conducted using structural equation modeling (SEM) and multiple linear regression. The results showed that influencer source credibility positively influences the attitudes of social media users (Generation Z), increasing their intention to visit recommended tourist destinations. In addition, influencer following behavior strengthens the relationship between social media usage goals and visit intention. The findings provide insights for the tourism industry in crafting more effective digital marketing strategies, utilizing influencers as a more personalized and experiential promotional tool.